A Case Series and Review of Bisphosphonate-associated Orbital Inflammation. (3rd March 2016) - Lefebvre, Daniel R.; Mandeville, John T.; Yonekawa, Yoshihiro; Arroyo, Jorge G.; Torun, Nurhan; Freitag, Suzanne K.
Abstract: Purpose : To report the largest series of new cases to date of bisphosphate-associated orbital inflammation. Methods : A retrospective case review of patients with orbital inflammation following treatment with systemic bisphosphonate. Results : Six patients over an 18-month period (2 males, 4 females) with an average age of 62.2 years had onset of orbital inflammatory symptoms 1–11 days after intravenous bisphosphonate infusion or, in 1 case, 4 weeks after initiation of oral bisphosphonate therapy. Imaging revealed diffuse orbital involvement in 3 cases, isolated lateral rectus muscle involvement in 2 cases, and superior rectus–levator involvement in 1 case. Two patients' symptoms resolved spontaneously within 2 weeks, and 3 responded rapidly and completely to corticosteroid therapy. The 1 patient on oral bisphosphonate had a slower but complete response to corticosteroid treatment. Conclusion : Clinicians should be aware of the association between acute orbital inflammation and recent treatment with systemic bisphosphonate medication.